FAKTOR EKSPLOITASI DI HUTAN ALAM DIPTEROKARPA PULAU LAUT - Apul Sianturi; Ishemat Soerianegara; Rahardjo S; Suparto Suparto; Syafii Manan (Jurnal Penelitian Hasil Hutan, 1984)
An investigation on the “exploitation  factor"  in the natural dipterocarp forest of Pulau Laut, South Kalimantan was carried out in 1981.  Sixty tree with a diameter at breat  height from 50  to 160  cm were selected at a sample from the stands in north and central Pulau Laut.                                                                                                                                  From the investigation the following conclusions are in order  : The logging waste in the natural dipterocarp forest of Pulau Laut is 20 percent, with a standard error of 1,4 percent. Exploitation factor in the Pulau Laut natural dipterocarp forest ranges from 76,8 to 82,4 percent, averaging 80 percent.The volumes of the trees obtained by estimating the diameters at breast height and the heights of the clear boles are consistanly smaller than those obtained by measuring the dimateres and lengths of the clear boles after the trees were cut especially in hilly forests. Both diameter and clear bole length have significant effect on exploitation factor, their relationship being quadratic.Optimum diameter for highest yield is approximately 77 cm. This however, requires further research especially in relation with silviculture and felling cycle.